Developmental Analysis of Compound Leaf Development in Arachis hypogaea - Sun, Ruiqi; Peng, Zhenying; Li, Shuangshuang; Mei, Hongyao; Xu, Yiteng; Yang, Wenying; Lu, Zhichao; Wang, Hongfeng; Zhang, Jing; Zhou, Chuanen (Frontiers in Plant Science, 2022)
Leaves are the primary photosynthetic structures, while photosynthesis is the direct motivation of crop yield formation. As a legume plant, peanut (Arachis hypogaea) is one of the most economically essential crops as well as an important source of edible oil and protein. The leaves of A. hypogaea are in the tetrafoliate form, which is different from the trifoliate leaf pattern of Medicago truncatula, a model legume species. In A. hypogaea, an even-pinnate leaf with a pair of proximal and distal leaflets was developed; however, only a single terminal leaflet and a pair of lateral leaflets were formed in the odd-pinnate leaf in M. truncatula. In this study, the development of compound leaf in A. hypogaea was investigated. Transcriptomic profiles revealed that the common and unique differentially expressed genes were identified in a proximal leaflet and a distal leaflet, which provided a research route to understand the leaf development in A. hypogaea. Then, a naturally occurring mutant line with leaf developmental defects in A. hypogaea was obtained, which displayed a pentafoliate form with an extra terminal leaflet. The characterization of the mutant indicated that cytokinin and class I KNOTTED-LIKE HOMEOBOX were involved in the control of compound leaf pattern in A. hypogaea. These results expand our knowledge and provide insights into the molecular mechanism underlying the formation of different compound leaf patterns among species.